An application of ergodic theory to Geometric Ramsey theory - Şimşek, Sevim. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
In this thesis we first present two examples from Geometric Ramsey theory in R2. Then we generalize these results to higher dimensions and construct our main theorem. Then we translate our geometric problem into dynamical form. Finally we prove the main theorem by using methods from ergodic theory.
Keywords: Ramsey theory.; Ergodic theory.